"Not to offer himself again and again": an exegetical and theological study of repetition in the letter to the Hebrews - Moore, NJ (2014)
Repetition has received a bad press in certain streams of theological tradition; this reception has in part been caused by, and has in turn affected, readings of the Letter to the Hebrews, which speaks about repetition in ways unique in the New Testament. The present study addresses the insufficient critical attention paid to repetition in Hebrews, challenging the assumption that it functions uniformly and negatively throughout the letter, and exploring the variety of ways in which Hebrews presents repetition. The plurality of prophetic speech displays God’s manifold kindness in the old covenant; such speech is not opposed to but is fulfilled in Christ’s coming, and its ongoing repetition in the new covenant through citation and exposition serves to promote and explicate that event. Repeated mutual encouragement is essential to persevering in the Christian life and avoiding apostasy. And the regular entry of the Levitical priests into the outer sanctuary of the tabernacle in Heb 9.6 foreshadows the continual access to God achieved through Christ. Where repetition has a negative or contrastive role in the author’s argumentation, it does not cause inefficacy but rather indicates a weakness whose source is elsewhere – and which, moreover, is revealed fully only in the light of the Christ event. The uniqueness of Christ and of his death construed as a sacrifice, developed from concepts of singularity in Day of Atonement and early Christian crucifixion traditions, forms a unifying strand in the letter’s Christology. Rather than functioning in simple opposition to repetition, this singularity corresponds to continuity and eternity, and is developed at times in contrast to, and at times in correspondence with, repetition. The study thus offers a reappraisal of repetition in Hebrews, laying the foundations for renewed appreciation of the importance of repetition for theological discourse and religious life.